Azithromycin for unscheduled cesarean delivery. Issue 11 (November 2017) - Flaherty, Allison; Castelli, Gregory
Abstract : N/A: Tita AT, Szychowski JM, Boggess K, Saade G, Longo S, Clark E, et al. Adjunctive azithromycin prophylaxis for cesarean delivery. N Engl J Med . 2016; 375(13):1231–1241.